Global and Planet Development Models: Theories, Models, Evaluation, and Vision - Dastagiri, M.B. (European Scientific Journal, ESJ, 2023)
The transformation of global development models from industrialization, technocratic, scientific, and information to economic and free trade models are emerging in the globalization era. Fundamentally, theories of development explore reasons for poor countries and their strategies towards development, which rich and poor countries adopt in order to alleviate the poorest. Many thinkers, economists, philosophers, and scientists are unable to confirm the best models for global development models. This paper focuses on analyzing models, theories, and rationales to find out about the global and planet development models. The study period is from 1944 to 2020. Theories of development originate from modernist model, dependency model, and post development model. According to modernization theory, a number of internal barriers are the reasons why â€˜third worldâ€™ countries are poor. Dependent theory states that poverty in developing countries is due to a 400-year history of colonialism and slavery. World systems theory argues that countries are underdeveloped due to history of extractive institutions. Neoliberalism philosophy, as a path of development, involves free trade, less government interference, and fewer restrictions on business. As per post development theory principles, development must have social justice, inclusivity, and sustainability. UN model for sustainable development is achieving economic and social development without environmental damage. Globalization theory is a process whereby the world becomes more interconnected. The role and models of international organizations adopted for global development are TNCâ€™s western capitalist-industrialist development model, WTO facilitating free trade based on US-led capitalist model, World Bank funds development in poor countries and adopted neo-liberalism model in third world countries, IMF- global sustainable economic growth and stability model, and UNO-Worldwide cooperation and coordination model to solve international economic, social, cultural, and humanitarian problems. Although man journeys to planets because of abundant economic resources floating up in space, Mars’s colonization interest is because of its similarities to earth. The moon industrialization rationality comprises of building materials, water, fuel, oxygen, and other useful resources. The results show planet development model such as planet agriculture model, space economy model, colonization of mars and industrialization of moon, and global multilateral initiations. The UN, World Bank, IMF, WTO, and TNCs should also use the prophecy of â€œThink Universally and Act regionally and locallyâ€. The future global and planet development model includes transformation from industrialization, technocratic, scientific, free trade, information, and economic models to knowledge intensive, space economy (network and solar energy), mars colonization, and moon industrialization which are the new future models.